Balancing selection for aflatoxin in Aspergillus flavus is maintained through interference competition with, and fungivory by insects. Issue 1869 (20th December 2017) - Drott, Milton T.; Lazzaro, Brian P.; Brown, Dan L.; Carbone, Ignazio; Milgroom, Michael G.
Abstract : The role of microbial secondary metabolites in the ecology of the organisms that produce them remains poorly understood. Variation in aflatoxin production by Aspergillus flavus is maintained by balancing selection, but the ecological function and impact on fungal fitness of this compound are unknown. We hypothesize that balancing selection for aflatoxin production in A. flavus is driven by interaction with insects. To test this, we competed naturally occurring aflatoxigenic and non-aflatoxigenic fungal isolates against Drosophila larvae on medium containing 0–1750 ppb aflatoxin, using quantitative PCR to quantify A. flavus DNA as a proxy for fungal fitness. The addition of aflatoxin across this range resulted in a 26-fold increase in fungal fitness. With no added toxin, aflatoxigenic isolates caused higher mortality of Drosophila larvae and had slightly higher fitness than non-aflatoxigenic isolates. Additionally, aflatoxin production increased an average of 1.5-fold in the presence of a single larva and nearly threefold when the fungus was mechanically damaged. We argue that the role of aflatoxin in protection from fungivory is inextricably linked to its role in interference competition. Our results, to our knowledge, provide the first clear evidence of a fitness advantage conferred to A. flavus by aflatoxin when interacting with insects.